TIME, RESISTANCE, AND SUSTAINABILITY: THE AKWẼ-XERENTE WORLDVIEW AS A FRAMEWORK FOR PUBLIC POLICIES AND INTERCULTURALITY - Caio Graco Santos Flor; Adriana da Costa Pereira Aguiar; Armando Sopre Xerente; Lucas Alves Martins; Shirley Pereira da Silva; Patrícia Gomes de Sousa Nunes; Geyciane Dos Santos Assunção Silveira; Maria Elenita Moura; Rita Pereira Aguiar Soares; Cláudia Lustosa Campos Diniz; Maria Antônia Martins Vanderlei de Sousa; Romário da Silva Cabral; et al. (Artefactum - revista de estudos interdisciplinares, 2026)
This study addresses the concept of time in Akwẽ-Xerente culture, highlighting its centrality in the construction of a cyclical worldview that connects natural, social and spiritual dimensions. The investigation explores how this temporality shapes traditional practices and how it adapts to contemporary dynamics, without losing its cultural essence. The analysis demonstrates that, although challenges are imposed by public policies, schooling and modern technologies, the Akwẽ-Xerente have given new meaning to these external influences in order to preserve their identity. Furthermore, the work discusses practical applications of the concept of Akwẽ-Xerente time in areas such as education, health and sustainability, highlighting its relevance for strengthening its culture and contributing to global issues. Despite the study's limitations, such as the absence of field data and the dependence on secondary sources, it offers a broad overview of the interactions between temporality and modernity, while at the same time highlighting the cultural resilience of the Akwẽ-Xerente. Recommendations for future research include more specific and comparative approaches, as well as investigations aimed at the integration between traditional knowledge and inclusive public policies.